2017
DOI: 10.3766/jaaa.16138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Device on Video Head Impulse Test (vHIT) Gain

Abstract: Numerous video head impulse test (vHIT) devices are available commercially; however, gain is not calculated uniformly. An evaluation of these devices/algorithms in healthy controls and patients with vestibular loss is necessary for comparing and synthesizing work that utilizes different devices and gain calculations.Using three commercially available vHIT devices/algorithms, the purpose of the present study was to compare: (1) horizontal canal vHIT gain among devices/algorithms in normal control subjects; (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 22 publications
4
34
0
1
Order By: Relevance
“…Saccades were not present in the study groups, a fact that agrees with the literature since the saccades reveal labyrinth hypofunction and are considered signs of pathology (1,2,4,5,13,(17)(18)(19)27,28,29) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Saccades were not present in the study groups, a fact that agrees with the literature since the saccades reveal labyrinth hypofunction and are considered signs of pathology (1,2,4,5,13,(17)(18)(19)27,28,29) .…”
Section: Discussionsupporting
confidence: 89%
“…The gains of all the semicircular canals presented means close to 1, thus confirming the findings of other studies where healthy individuals were evaluated (7,11,13,(18)(19)(20) . Mossman et al (21) also reported gain values near 1 in 60 individuals without otoneurological alterations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There is a modest literature ( 73 , 75 , 115 , 117 ) suggesting that vHIT can play a valuable role in the identification of BVW, but its sensitivity and specificity (compared with the gold standard of RCT) has yet to be established. Comparison of vHIT with RCT is complicated by several factors that can introduce variability into calculation of VOR gain on vHIT; the first reason is physiologic, and has to do with the fact that target viewing distance (which may not be carefully controlled) can have a significant effect on gain both in healthy individuals ( 118 120 ) and in patients with peripheral vestibular disease ( 121 ); the second reason is technological, as it has been demonstrated that different devices and different algorithms can render different results in gain ( 122 ).…”
Section: Bvw: Vestibular Laboratory Testingmentioning
confidence: 99%
“…Salienta-se que, apesar do uso do vHIT ser comprovadamente útil para a avaliação da população infantil, observou-se falta de consenso entre os pesquisadores em relação aos resultados e à aplicabilidade do exame (HÜLSE et al, 2015;MATIÑO-SOLER et al, 2015;ROSS;HELMINSKI, 2016;ALIZADEH et al, 2017;LEHNEN et al, 2017;WIENER, 2017;BACHMANN et al, 2018;JANKY;RODRIGUES, 2018 ).…”
Section: Discussionunclassified